Comparison of Modified Retroperitoneal Adrenalectomy With the Gold Standard for Benign Adrenal Tumors. Issue 1 (February 2016) - Hu, Dongliang; Wang, Xinghuan; Liu, Tongzu
Abstract : Objectives: To compare our modified retroperitoneoscopic adrenalectomy with the standard procedure. Methods: A total of 68 patients underwent modified retroperitoneoscopic adrenalectomy. Simultaneously, another 23 patients were treated using the standard procedure. The demographic data and perioperative outcomes of the patients were obtained for statistical analysis. Results: No significant differences in age, evaluated blood loss, oral intake, and hospital stay were observed. The mean operation time in the modified group was shorter than that in the standard group (58.3±16.4 vs. 79.5±23.6 min, P <0.05). The median total length of incision was shorter in the modified group than in the standard group (4.5±0.8 vs. 6.4±1.1 cm, P <0.05). The modified group also showed significantly better pain control (3 vs. 6 diclofenac sodium use, P <0.05) and cosmetic outcome (score, 9.1±1.8 vs. 8.2±2.1, P <0.05) than the standard group. Conclusions: Our modified retroperitoneoscopic adrenalectomy is a safe and alternative procedure for adrenal tumors. This procedure offers superior cosmetic outcome, better pain control, and shorter operation time compared with the standard retroperitoneal adrenalectomy.